Identity Recognition in Education: A Philosophical Framework for Addressing Bullying in Indonesia - Setia Paulina Sinulingga; Rr. Siti Murtiningsih; Hatanti Widy Nugroho (STAI Hubbulwathan Duri, 2025)
Bullying in schools remains a critical yet often underestimated issue, negatively affecting victims and disrupting the broader educational environment. Its long-term consequences include psychological trauma, low self-esteem, and hindered social-emotional development. Addressing bullying requires a comprehensive, value-based approach. This study integrates Charles Taylor’s theory of recognition with educational philosophy to explore bullying prevention strategies. Conducted at SMA Negeri 2 Tanjung, South Kalimantan, the research examines how applying recognition-based principles can foster a more inclusive and respectful school culture. The implementation of recognition-oriented practices significantly improved relationships among students and between students and teachers. Findings indicate a reduction in bullying incidents, alongside notable increases in student self-esteem, social integration, and mutual respect. Students reported feeling more acknowledged and valued, contributing to a more harmonious school environment. These outcomes highlight the potential of a recognition-based framework in addressing bullying. Emphasizing individual identity and diversity helps cultivate an inclusive culture where mutual respect is central. While the study focuses on one school, its implications are relevant for broader educational contexts across Indonesia.